PENGGUNAAN MODEL PEMBELAJARAN KOGNITIF MORAL DALAM MENINGKATKATKAN KEBERANIAN MENGEMUKAKAN PENDAPAT DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PKN DI KELAS VIII C SMP NEGERI 31BANJARMASIN - Annisa Norjanah (Jurnal Pendidikan Kewarganegaraan, 2014)
The learning process VIIIC Civics in the Junior High School 31 Banjarmasin tend not achieve the expected results . Poor condition courage students to express opinions affects the quality of learning in the classroom . Learning that takes place in a class of students who are good looks alone were active when expressed opinion, this situation results in students who are still not familiar with the material described teachers feel embarrassed to ask and express their opinions because they feel unappreciated . Lack of courage students to express opinions can be seen from the low courage students to express opinions in the group discussions . Students pay less attention to the teacher explaining and self-absorbed , only a few students were able to catch the teacher explained the material. This resulted in poor learning outcomes. The purpose of the study was : (1) To determine the activity of teachers in applying the cognitive model of moral learning in the classroom VIIIC SMP 31 Banjarmasin (2) To improve siswaq courage to express opinions on civics lesson in the application of moral cognitive model of learning in the classroom VIIIC SMP 31 Banjarmasin (3) to improve student learning outcomes in applying the model of learning in the classroom CognitiveMoral VIIIC SMP 31 Banjarmasin. Data collection techniques used in action research (PTK) is the observation , documentation and test results of study conducted through several cycles , the first cycle and second cycle. The results of this study indicate (1) Teaching teachers to implement cognitive learning model of moral place smoothly . In the first cycle of learning in teacher qualifications good enough and the second cycle has increased very well with good qualifications . (2) Courage students increased expression very well with good qualifications . (3) applying the learning process can improve the cognitive model of moral courage to express opinions .